C.A. Larsen - Pioneer of the Antarctic ocean - Devig, Thor N (Norwegian maritime explorers and expeditions : over the past thousand years, 1999)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Sørishavet; historie; hvalfangst; kartlegging; oppdagelsesreiser; pelagisk; polarekspedisjoner

Søylegangen i Buenos Aires - Fløgstad, Kjartan (Eld og vatn : nordmenn i Sør-Amerika, 1999)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Roald Amundsen; hvalfangere; hvalfangstindustri; oppdagelsesreiser; pelagisk

Roald Amundsen : en biografi - Bomann-Larsen, Tor (Cappelen, 1998)
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolen; biografi; ekspedisjoner; oppdagelsesreiser

Noruega y las regiones polares - Hansson, Rasmus (Real Ministerio Noruego de Asuntos Exteriores, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norvegija i poljarnye rajony - Hansson, Rasmus (Izdano Ministerstvom inostrannych del Norvegii, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norway and the polar regions - Hansson, Rasmus (The Royal Norwegian Ministry of Foreign Affairs, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Norwegen und die Polargebiete - Hansson, Rasmus (Kgl. Norwegisches Ministerium für Auswärtige Angelegenheiten, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Klarius Mikkelsen's 1935 landing in the Vestfold Hills, East Antarctica: some fiction and some facts - Norman, Frederick Ian; Gibson, John A E; Burgess, J S (Polar Record, 1998)
Exploratory activities of Norwegians, particularly those directed by Lars Christensen, off eastern Antarctica are discussed briefly in relation to contemporary Antarctic investigations and politics. The interests of Norway there and Christensen's role in establishing an understanding of the local coastline are indicated. Particular attention is paid to the landing made by Klarius Mikkelsen in the Vestfold Hills, East Antarctica, on 20 February 1935. Note is taken of the site's recent re-discovery, and the symbolic role of the landing in the national aspirations of Norway, Britain, and Australia is discussed. Mikkelsen operated under commercial and scientific interests promoted by Christensen, and his landing was, at least in published material, seen as an extension of them. However, there is a suggestion that not only had a new Norwegian land been discovered, and a landing made, but that a claim to it was at least considered. Such a claim was not appropriate given previous agreements between Norway and Britain. The site's location and environs are discussed, as are subsequent flights over it and visits made there by Australian expeditioners. The ambiguity associated with claims that Caroline Mikkelsen was the first woman to land on the Antarctic mainland is also examined. Since Mikkelsen's site was on an island within the Tryne Group, to the north of Davis station, if a mainland location is required to establish such an event, then an alternative (Scullin Monolith) is proposed; however, on this occasion four women were involved, but who was first ashore remains uncertain.
Keywords: Antarktis; Nordmenn; Thorshavn ekspedisjon; første landgang; kvinner; oppdagelsesreiser

Den tredje mann : beretningen om Hjalmar Johansen - Kvam, Ragnar (Gyldendal, 1997)
Keywords: Antarktis; Nordmenn; Sydpolsekspedisjonen; biografier; oppdagelsesreiser; polarekspedisjoner; polarhistorie

Sandefjords historie - Olstad, Finn (Sandefjord kommune, 1997)
Keywords: Nordmenn; Norge; Sørishavet; Vestfold; historie; hvalfangere; hvalfangst; hvalfangstindustri; hvalindustri

Cato mot Sydpolen - Hauge, Odd Harald; Bry, Knut; Ebbesen, Lars (Pax, 1995)
Keywords: Antarktis; Nordmenn; Sydpolen; ekspedisjoner; fotokunst; funksjonshemmede; oppdagelsesreiser; polarekspedisjoner; reiser; reiseskildringer

The Vestfold Hills: the Norwegian connection - Patterson, D (ANARE News, 1995)
Keywords: Antarktis; Nordmenn; ekspedisjoner; oppdagelsesreiser

A century of German interests in modern whaling, 1860s-1960s - Barthelmess, Klaus (Whaling and history : perspectives on the evolution of the industry, 1993)
Keywords: Nordmenn; Sørishavet; Tyskland; hvalfangere; pelagisk hvalfangst; økonomi

Vel blåst! Kommandør Chr. Christensens Hvalfangstmuseum gjennom 75 år 1917-1992 - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1992)
Keywords: Antarktis; Christen Christensen; Nordmenn; Vestfold; historie; hvalfangere; hvalfangstindustri; pelagisk; polarekspedisjoner

Ingeniør Sæbjørnsens bukspretter - Ringstad, Jan Erik (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Keywords: Nordmenn; Sørishavet; hvalfangst; hvalfangstindustri; hvalindustri; patenter; pelagisk; utstyr

På hvalfangst med blyant og farvestifter - Wexelsen, Einar (Utkikksposten (Sandefjord) : kontaktorgan for Sandefjordmuseene, 1990)
Keywords: Nordmenn; Sørishavet; historie; hvalfangst; kunst; pelagisk

Norway's polar territories - Barr, Susan (Aschehoug, 1987)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Peter I. Øy; geografi; geologi; historie; polarområdene; polarpolitikk

Rosshavets base på Stewart Island - Hoff, Stein (Norsk sjøfartsmuseum. Årsberetning, 1987)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; historie; hvalfangere; hvalfangststasjoner; pelagisk

Oppfinere og teknologisk utvikling i norsk hvalfangsthistorie - Basberg, Bjørn L (Sandefjordmuseene. Årbok, 1986)
Keywords: Antarktis; Nordmenn; Norge; harpuner; historie; hvalfangere; hvalfangst; hvalfangstindustri; hvalindustri; patenter; pelagisk

Noen norske stedsnavn på Syd Georgia - Thoresen, Per (Sandefjordmuseene. Årbok, 1986)
Keywords: Antarktis; Nordmenn; historie; hvalfangere; hvalfangstindustri; hvalfangststasjoner; hvalindustri

Eventyret om hvalfangsten - Christensen, Nils Steen; Hagelund, Olav (Stokke bygdebok, 1983)
Keywords: Nordmenn; Sørishavet; Vestfold; arbeidsforhold; hvalfangere; hvalfangst; pelagisk

Norge i polarområdene - Egeland, Knut (Leif Holtedahls forl., 1982)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Smia på Fevang - Thoresen, Per (Vestfoldminne, 1976)
Keywords: Nordmenn; Sørishavet; erindringer; hvalfangere; hvalfangst; pelagisk

På hvalfangst med Salvesen - Asplin, Tore (T. Asplin, 1974)
Keywords: Nordmenn; Sørishavet; erindringer; fortellinger; historie; hvalfangere; hvalfangst; pelagisk

Hvalfangst - Weyergang-Nielsen, Arthur (Larviks historie, 1963)
Keywords: Nordmenn; Sørishavet; Vestfold; historie; hvalfangere; hvalindustri; pelagisk

Spotlight on the Antarctic - Friis, Erik J (The American-Scandinavian Review, 1962)
Omhandler 50 års-jubileet for Sydpolens erobring, med bl.a. overrekkelse av minneplakett, og Tore Gjelsvik til stede.
Keywords: Antarktis; Nordmenn; Norsk Polarinstitutt; Roald Amundsen; Sydpolsekspedisjonen

Femti år i konkurranse og fremgang : aktieselskapet Tønsbergs Hvalfangeri 1907-1957 - Wasberg, Gunnar Christie (Tønsbergs Hvalfangeri. Styret, 1958)
Keywords: Nordmenn; Norge; Sørishavet; historie; hvalfangere; hvalfangstindustri; hvalfangstselskaper; hvalindustri; pelagisk

Norges skibsførere : 1935-1953 - Meling, Torjer (red.); Berg, Gabriel (red.); Bjønness, Henry (red.); Lindtner, N Fr. (red.) (Dreyer, 1954)
Keywords: Nordmenn; Sørishavet; biografier; historie; hvalfangere; hvalfangst; pelagisk; sjøfolk; skipsfart; skipsførere

Of whales and men - Robertson, R B (Knopf, 1954)
Keywords: Nordmenn; Sørishavet; ekspedisjon; hvalfangere; hvalfangst; pelagisk; sjøfolk

Hval og mannfolk - Robertson, R B; Stai, Arne (Gyldendal, 1954)
Keywords: Nordmenn; Sørishavet; ekspedisjon; hvalfangere; hvalfangst; pelagisk; sjøfolk

Speiderguttene som drog på hvalfangst - Amundsen, Sverre S (Aschehoug, 1953)
Keywords: Nordmenn; Sørishavet; fortellinger; hvalfangere; hvalfangst

Norske fangfstfolk og forskere i Antarktis. Den Tredje Framferda (1910-12). Mot Nordpolen via Sørpolen. Roald Amundsen planter den norske flagget på Sørpolen 14.-12.-1911 - Opsund, Enok (Nordmenn i polheimene, 1948)
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; fangst; forskning; polarområdene

Hvalfangst på sydfeltet i krigstiden - Vikestad, Arne (Tusen norske skip : en antologi over norske sjøfolks innsats i den annen verdenskrig, 1948)
Keywords: Nordmenn; Sørishavet; Verdenskrigen 1939-45; ekspedisjoner; erindringer; hvalbåter; hvalfangst; pelagisk

Norwegian patents relating to whaling and the whaling industry : a statistical and historical analysis - Johnsen, Arne Odd (A. W. Brøggers Boktrykkeri A/S, 1947)
Keywords: Nordmenn; Norge; Sørishavet; harpuner; hvalfangere; hvalfangst; hvalfangstindustri; hvalindustri; patenter; pelagisk; økonomi

Fra Spitsebergisen til Sydhavsbrisen - Stavseth, Reidar (Arven fra Bjørn Farmann : Tønsberg Sjømannsforening gjennom 100 år, 1946)
Keywords: Nordmenn; Sørishavet; historie; hvalfangst; pelagisk; sjøfolk

Olav Bjåland : idrottsmann og polfarar - Austbø, Johan (Fonna, 1945)
Keywords: Antarktis; Nordmenn; Sydpolsekspedisjonen; biografier; polarekspedisjoner; polfarere

Roald Amundsen - Wilse, Anders Beer (Norsk landskap og norske menn, 1943)
Keywords: Antarktis; Nordmenn; Roald Amundsen; Sydpolsekspedisjonen; biografier

Hjemkomsten. Hvlafangsten historie fra dens første begynnelse - Istre, Henry R (Hvalfangstliv : spesialorgan for hvalfangst, 1937)
Keywords: Antarktis; Carl Anton Larsen; Nordmenn; Sørishavet; historie; hvalfangere; hvalfangst; pelagisk

Atlas over Antarktis og Sydishavet : utgitt av Hvalfangernes Assuranceforening i anledning av foreningens 25-års jubileum - Hansen, Hans Edvard (red.) (Hvalfangernes Assuranceforening, 1936)
Keywords: Antarktis; Nordmenn; Norge; Sørishavet; hvalfangst; kartlegging; norske ekspedisjoner; oppdagelsesreiser

Kartskisse av nyopdaget kyststrekning mellem 72° og 81° ost lengde samt M/T Thorshavnsfører, kaptein Klarius Mikkelsen, Mars 1935 - Heyerdahl, Eilif Fredrik (1936)
Keywords: Antarktis; Nordmenn; ekspedisjoner; oppdagelsesreiser

Norges skibsførere : 1933-1935 - Meling, Torjer (red.); Berg, Gabriel (red.); Gausel, Arnold Chr. (red.); Dreyer, Paul (red.) (Dreyer, 1935)
Keywords: Nordmenn; Sørishavet; biografier; historie; hvalfangere; hvalfangst; pelagisk; sjøfolk; skipsfart; skipsførere

Norwegian Discoveries in the Antarctic, 1935 - [Mikkelsen, Klarius] (Polar Record, 1935)
Keywords: Antarktis; Nordmenn; ekspedisjoner; oppdagelsesreiser

Walfang und Forschung in der Antarktis - Steinert, Hermann (Geographische Zeitschrift, 1933)
Keywords: Antarktis; Nordmenn; Norge; Norvegia ekspedisjonene; forskning; hvalfangst; pelagisk

Våre polarflyverferder i nord og syd - Arnesen, Odd (Til veirs på norske vinger : av flyvningens historie i Norge, 1930)
Keywords: Antarktis; Bouvetøya; Finn Lützow; Hjalmar Riiser Larsen; Holm; Nordmenn; Norge; Norvegia ekspedisjonen; biografier; historie; kartlegging; luftfart

Norwegian exploration: Expeditions of 1926-1929 - Joerg, W L G (Brief history of polar exploration since the introduction of flying, 1930)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Lars Christensen; Nordmenn; Norvegia ekspedisjoner; Peter I. Øy; flyvninger; oppdagelsesreiser; vitenskapelige ekspedisjoner

Eventyret om den norske hvalfangst : i tekst og billeder - Overn, Ole Martin (Stranberg, 1929)
Keywords: Nordmenn; Norge; Svend Foyn; Sørishavet; hvalfangere; hvalfangst

Hvalfangst i Sydhavet - Mørch-Olsen, Øistein (Tønsbergs Forlag, 1925)
Keywords: Nordmenn; Sørishavet; hvalfangere; hvalfangst; pelagisk

På valfångst i Södra Ishavet - Nielsen, Aage Krarup; Larsson, Robert (Hugo Geber, 1922)
Keywords: Nordmenn; Sørishavet; ekspedisjoner; hvalfangere; hvalfangst; norske; pelagisk

Johan Koren : (4. oktober 1879 - 4. mars 1919) - Schaanning, Hans Thomas Lange (Norsk Jæger- og Fisker-Forenings Tidsskrift, 1920)
Keywords: Antarktis; Belgica ekspedisjon; Johan Koren; Nordmenn; oppdagelsesreiser; polarforskning; zoologi

Modern whaling & bear-hunting : a record of present-day whaling with up-to-date appliances in many parts of the world, and of bear and seal hunting in the Arctic regions - Burn Murdoch, William Gordon (Seeley, Service & Co., 1917)
Keywords: Nordmenn; Norge; Sørishavet; hvalfangere; hvalfangst; norsk; pelagisk; selfangst

The Antarctic question : voyages to the South Pole since 1898 - Machat, J (Annual Report Smithsonian Institution, 1908)
Keywords: Antarktis; Carl Anton Larsen; Carsten Egeberg Borchgrevink; Nordmenn; Sydpolsekspedisjoner; hvalfangere; hvalfangst; oppdagelsesreiser